The Formulation of Echo Sounding Correction Tables - Zheng, Guan (The International Hydrographic Review, 2015)
The ‘Echo Sounding Correction Tables’ (formerly Matthews’ Tables) are of important practical use to hydrographers, and are convenient to use. In case that there is not any oceanographic data available, the actual depth is derived from the tables with the observed depth from the echo sounder. With the recommendation of the International Hydrographic Organization (IHO) and the Hydrographic Offices of some countries, the tables have been widely used in recent years. Matthews’ tables are suitable for the manual correction of sounding velocity, but not for use by computers. In this paper, the tables are formulated by using the method of the least squares approximation on the basis of the orthogonal system of polynomials. So that only a few simple coefficients need to be entered into the computer, and then the true depth can be calculated directly on the basis of the observed depth data. These correction formulas are very easy and efficient to use, and their accuracy is equivalent to that of the ‘Echo Sounding Correction Tables’.